A Novel Small-Molecule Inhibitor of Mcl-1 Blocks Pancreatic Cancer Growth In vitro and In vivo - Abulwerdi, Fardokht (2013)
Using a high throughput screening (HTS) approach, we have identified and validated several small molecule Mcl-1 inhibitors (SMIs). Here we describe a novel selective Mcl-1 SMI inhibitor, 2 (UMI-77), developed by structure-based chemical modifications of the lead compound 1 (UMI-59). We have characterized the binding of UMI-77 to Mcl-1 by using complementary biochemical, biophysical and computational methods, and determined its antitumor activity against panel of pancreatic cancer (PC) cells and in vivo xenograft model. UMI-77 binds to the BH3 binding groove of Mcl-1 with K(i) of 490 nM, showing selectivity over other members of anti-apoptotic Bcl-2 members. UMI-77 inhibits cell growth and induces apoptosis in PC cells in a time and dose-dependent manner, accompanied by cytochrome c release and caspase-3 activation. Co-immunoprecipitation experiments revealed that UMI-77 blocks the heterodimerization of Mcl-1/Bax and Mcl-1/Bak in cells, thus antagonizing the Mcl-1 function. The Bax/Bak-dependent induction of apoptosis was further confirmed by using murine embryonic fibroblasts that are Bax and Bak deficient. In an in vivo BxPC-3 xenograft model, UMI-77 effectively inhibited tumor growth. Western blot analysis in tumor remnants revealed enhancement of pro-apoptotic markers and significant decrease of survivin. Collectively, these promising findings demonstrate the therapeutic potential of Mcl-1 inhibitors against PC and warrant further preclinical investigations.